Desain dan Kinerja Sistem Pneumatik untuk Penabur Pupuk Tanaman Sawit Muda - Muqroob Tajalli; Wawan Hermawan; Radite Praeko Agus Setiawan (Jurnal Keteknikan Pertanian, 2016)
AbstractCurrent Mechanical fertilizer applicators using centrifugal spreading system could not be applied to young palm oil trees (under 5 years old) and hence needed to be modified. The research was to design a fertilizer spreading system, using a pneumatic system. The design used a positive type pneumatic pressure to blow the granular fertilizer out of the metering device to the soil surface around the tree. The metering device was designed to deliver the fertilizer in several application rates, i.e.: 0.25, 0.75, 1.0, 1.25, and 1.5 kg/tree. Based on pressure drop analysis the pneumatic system needed a power of 0.71 kW, where the blower should be rotated at 3000 rpm to produce an air flow of ± 0.3375 m3/s. A This prototipe spreader was tested in the field at 0.55 and 1.7 m/s forward speed one at a time. Test results showed that the spreader could deliver the fertilizer to the targetted area around the palm oil trees with an accurate application rate. However, the distribution of the fertilizer was relatively low at a range of coefficient of variance of 0.47-0.77.AbstrakMesin pemupuk yang menggunakan mekanisme gaya sentrifugal, perlu dimodifikasi, karena tidak dapat diaplikasikan untuk memupuk tanaman kelapa sawit belum menghasilkan (di bawah 5 tahun). Penelitian ini dilakukan dengan merancang sistem penabur pupuk, menggunakan sistem pneumatik, dimana Penjatah pupuk didesain untuk menghembuskan pupuk pada beberapa dosis pemupukan, yaitu: 0.25, 0.75, 1.0, 1.25 dan 1.5 kg/tanaman. Berdasarkan analisis kehilangan tekanan, sistem pneumatik ini membutuhkan daya 0.71 kW pada putaran blower 3000 rpm yang menghasilkan aliran udara sebesar ±0.3375 m3/s.Prototipe penabur pupuk ini telah diuji di lapang pada kecepatan maju 0.55 m/s dan 1.7 m/s. Hasil pengujianmenunjukkan bahwa penabur pupuk ini dapat menghembuskan pupuk ke sasaran di sekitar tanamankelapa sawit dengan laju pemupukan yang akurat. Namun, sebaran pupuk relatif rendah dengan koefisien ragam antara 0.47 - 0.77.